Digitization path to improve ESG performance: A study on organizational perspectives. - Feifei Zhao; Zhipeng Han; Liguo Wang (PLoS ONE)
Digital technology development provides new opportunities for environmental, social, and governance (ESG) performance research to better evaluate firm ESG performance, improve decision-making efficiency, and enhance firm competitiveness. Therefore, under the background of digital economy, studying digitization mechanisms on ESG performance is of great theoretical and practical significance, which can help firms achieve better sustainable development and create more value for stakeholders. We use 3,827 listed A-share companies in China from 2003 to 2021 as the sample for our empirical research. Results show that digitization significantly improves ESG performance, and this conclusion remains valid after a series of robustness tests. Through mechanism analysis, we find that digitization improves ESG performance through organizational resilience and further reveal that organizational redundancy has a positive moderating effect between organizational resilience and ESG performance. According to our heterogeneity analysis, the marginal effects are stronger among listed firms with high market competition, in the East-Central region, in non-heavily polluting industries, and with standard audit opinions, without significant heterogeneity across the nature of equity. Our research provides a theoretical basis for digitization to drive ESG performance and ideas on how to improve the ESG performance of Chinese companies in the digital era.